2013
DOI: 10.1590/s1517-83822013000300031
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-associated methicillin-resistant Staphylococcus aureus carrying the PVL gene outbreak in a Public Hospital in Rio de Janeiro, Brazil

Abstract: Hospital associated methicillin-resist Staphylococcus aureus has long been associated to outbreaks in the hospital environment. In this work, we investigated an outbreak of Hospital associated methicillin-resist Staphylococcus aureus carrying the Panton-Valentine leukocidin gene, which occurred in a large community hospital in Rio de Janeiro, Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
4
1
Order By: Relevance
“…Surprisingly in this study, we found the PVL gene in SCCmec type III MRSAs often classified as HA-MRSA. This is in concordance with some previous findings that proved the sole existence of PVL is not a decisive clue for characterization of an MRSA as CA-MRSA (27)(28)(29)(30)(31). Havaei et al reported that the prevalence of PVL harboring isolates in five Hospitals of Tehran was 24.2%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Surprisingly in this study, we found the PVL gene in SCCmec type III MRSAs often classified as HA-MRSA. This is in concordance with some previous findings that proved the sole existence of PVL is not a decisive clue for characterization of an MRSA as CA-MRSA (27)(28)(29)(30)(31). Havaei et al reported that the prevalence of PVL harboring isolates in five Hospitals of Tehran was 24.2%.…”
Section: Discussionsupporting
confidence: 92%
“…It seems that PVL carrying phages were integrated into pre-existing endemic MRSA strains; therefore, a previously accepted hypothesis about markers of CA-MRSA strains could be speculated. Our findings and some previous studies suggest that the PVL gene could not be an appropriate marker for CA-MRSA (9,10,27,(37)(38)(39). Altogether, these findings are alarming with respect to the genetic background of these HA-MRSA strains (ST239/SCCmec III), since it is possible that these highly virulent strains spread to other hospitals in various geographical regions.…”
Section: Discussioncontrasting
confidence: 53%
“…Although the properties of CA-MRSA appear to make it less aggressive than hospital clones, the OSP clone presents virulence factors involved in the high pathogenicity, such as the PVL, which kills immune cells and induces tissue necrosis [ 82 , 83 , 86 , 87 , 89 , 90 ]. Although originally found in MRSA SCC mec type IV, PVL has also been reported in strains with other types of cassettes mostly present in HA-MRSA strains, such as BEC, due to a horizontal transfer of genes [ 29 , 63 , 91 , and 92 ]. Such horizontal transference indicates contact between CA and HA-MRSA.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of MRSA strains are circulating in different hospitals and communities in Brazil, as well as worldwide [ 22 , 23 , 24 , 25 , 26 ]. Although the Brazilian Epidemic Clone (BEC) (ST239 SCC mec III) remains circulating in different hospitals and the community in our country [ 27 , 28 ], previous studies have shown the substitution of this clone for others, such as the New York/Japan clone (USA100/ST5/CC5/SCCmecII), community-acquired MRSA (USA300/ST8/CC8/SCCmecIV), and pediatric clone (USA800/ST5/CC5/SCCmecIV) [ 2 , 3 , 4 , 29 ]. This fact has evidenced the need for studies on the epidemiological, microbiological, and genetic characteristics of these microorganisms to improve and better understand the pathogen evolution, the scenario changes, and update control measures.…”
Section: Introductionmentioning
confidence: 99%